ASSISTANCE OF ENGLISH TEACHERS IN TOEIC TEST PREPARATION FOR 12TH CLASS STUDENTS WITH ONLINE LEARNING STRATEGIES - Titin Kustini; Afief Fakhruddin Afief Fakhruddin (Universitas Majalengka, 2022)
To improve the competence of vocational students, the Ministry of Education and Culture provides free TOEIC test facilities for vocational students through the SMK ENGLISH CHALLENGE program: FACILITATION OF INTERNATIONAL CERTIFICATION OF ENGLISH LANGUAGE CAPABILITIES WITH TOEIC FOR SMK STUDENTS. SMKN 1 Kadipaten is one of the schools in Majalengka Regency that utilizes facilities from the Ministry of Education and Culture. To improve students' competence in order to obtain satisfactory TOEIC scores, English teachers at SMKN 1 Kadipaten are committed to implementing various mentoring methods for test-taking students. However, the test faced at least two obstacles, namely, coincided with school holidays and also the implementation of field work experience program so that direct guidance through face-to-face became impossible. This is certainly a problem that requires a good solution. This PKM program aims to assist English teachers at SMKN 1 Kadipaten to find effective ways to increase the TOEIC scores achieved by students. The method of implementing this program is carried out with a Forum Group Discussion approach to English teachers and is applied to students by utilizing social media and the online meeting application, Google Meet. At the end of the program, students are able to prepare themselves optimally both from a technical point of view, motivation and knowledge of the TOEIC test.